Evaluating the effects of synthetic POM cycles and NAD+ kinase expression on fatty alcohol production in Saccharomyces cerevisiae - Bonnie A. McNeil; Charfeddine Khalifa; Anagha Krishnan; David T. Stuart (PLoS ONE, 2025)
Efficient regeneration of NADPH can be a limiting factor for anabolic processes in engineered microbial cells. We tested the ability of four distinct Pyruvate-Oxaloacetate-Malate “POM” cycles composed of Saccharomyces cerevisiae pyruvate carboxylase (PYC1 or PYC2), malate dehydrogenase (‘MDH1 or ‘MDH2), and malic enzyme (sMAE1) to improve NADPH regeneration. Only the PYC1, ‘MDH2, sMAE1 combination increased the titer of fatty alcohols produced by engineered S. cerevisiae indicating that not all combinations of POM cycle enzymes could drive this pathway. Metabolomic analysis revealed that introduction of the POM cycle altered the concentration of intermediates in amino acid biosynthetic pathways and the trichloroacetic acid cycle suggesting that the POM cycle had wider effects than previously anticipated. Overexpression of the endogenous NAD+ kinases UTR1, YEF1, and a cytosolic version of POS5 were also tested. Only expression of POS5c resulted a significant increase in fatty alcohol titer. In these minimally engineered strains, combined overexpression of the PYC1, ‘MDH2, sMAE1 POM cycle and POS5c did not further increase titers. These findings indicate that more extensive metabolomic and proteomic investigations are required to identify combinations of enzymes that will yield an optimal increase in NADPH to meet anabolic demands without imposing excessive metabolic burden or disrupting pathways that might compromise bioproduct synthesis.